2010
DOI: 10.4103/0019-5545.74308
|View full text |Cite
|
Sign up to set email alerts
|

Pathway of care among psychiatric patients attending a mental health institution in central India

Abstract: Introduction:Only a limited proportion of patients with psychiatric disorders attend the healthcare facilities, and that too when the condition becomes severe. Treatment from unqualified medical practitioners and faith healers is a common practice, and is attributable to the delay in proper treatment.Materials and Methods:A cross-sectional study was conducted to understand the pathway of care adopted by psychiatric patients and its relationship with the socio-demographic determinants in the study population. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
143
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(164 citation statements)
references
References 14 publications
(17 reference statements)
17
143
3
1
Order By: Relevance
“…The average age of presentation in this study was 33.76 years, which was in accordance to previous studies showing that most patients belonged to 16 years to 45 years, 11 further strengthening the fact that the economically positive age group would seek mental health care more. There was equal representation by males and females, which refutes the gender bias in Indian society, and shows that equal importance has been given to males and females in seeking psychiatric care.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The average age of presentation in this study was 33.76 years, which was in accordance to previous studies showing that most patients belonged to 16 years to 45 years, 11 further strengthening the fact that the economically positive age group would seek mental health care more. There was equal representation by males and females, which refutes the gender bias in Indian society, and shows that equal importance has been given to males and females in seeking psychiatric care.…”
Section: Discussionsupporting
confidence: 91%
“…A study by Lahariya et al 11 found 68.5% of individuals seeking faith healers help as the first source, this could be due to poor understanding of mental disorders and the stigma associated with them. Twenty eight percent of patients presented with psychotic disorders, out of which 85.7% seek faith healers help at first.…”
mentioning
confidence: 99%
“…This difference was statistically significant; this was similar to findings of other studies which were done among geriatric patients in psychiatry healthcare and old age homes [6][7][8]. However, some studies [9] found that a majority of the patients with psychiatric morbidity were in the age group of 16-45 years and that most were suffering from severe mental illness; of which bipolar affective disorder (45%) and schizophrenia (35.9%) were the two most common ones. This may point to a trend where depressive disorders are more common in elderly and psychotic disorders are more common in the young.…”
Section: Discussionsupporting
confidence: 90%
“…Probably this reflects an increased popularity and acceptance of mainstream medicine over the years [14][15][16] due to its higher efficacy (compared to other methods of treatment) and its role in controlling the disorders associated with high stigma in Indian culture. Medical practitioners trained in mainstream medicine are now the first caregivers than the faith healer, though in some part of India vice versa is true [17][18][19] .…”
Section: Demographic and Clinical Characteristicsmentioning
confidence: 99%
“…It appears that depending upon the explanatory model of illness, patients sought a treatment method 26 . Those with a medical model continued with the next level of treatment (primary care to tertiary care) while those with non-medical model changed their strategy and shifted to the medical model after an inadequate response to the treatment 19 .…”
Section: Level Of Paranormal Beliefmentioning
confidence: 99%